Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Polymer-supported palladium-imidazole complex catalyst for hydrogenation of substituted benzylideneanilines - Udayakumar, V.; Alexander, S.; Gayathri, V.; Shivakumaraiah; Patil, K. R.; Viswanathan, B. (Journal of Molecular Catalysis A-Chemical, 2010)
The polymer-supported palladium-imidazole complex catalyst was synthesized and characterized by various techniques Such as elemental analysis, IR spectroscopy and TG analysis. The physico-chemical properties such as bulk density, Surface studies by BET method and swelling studies of catalyst in different solvents were investigated. XPS Studies were carried out to identify the oxidation state of palladium in the catalyst. The morphology of the support and the catalyst was studied using scanning electron microscope. Using the synthesized catalyst, hydrogenation of benzylideneaniline and a few of its para Substituted derivatives was carried out at ambient conditions. The influence of variation in temperature, concentration of the catalyst as well as the substrate on the rate of reaction Was Studied. The catalyst showed an excellent recycling efficiency over six cycles without leaching of metal from the polymer support. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Benzylideneaniline; Hydrogenation; kinetics; Polymer-supported palladium-imidazole complex catalyst